Rare pediatric tumors in Germany – not as rare as expected: a study based on data from the Bavarian Cancer Registry and the German Childhood Cancer Registry - Achajew, Aisana; Brecht, Ines B.; Radespiel-Troeger, Martin; Meyer, Martin; Metzler, Markus; Bremensdorfer, Claudia; Spix, Claudia; Erdmann, Friederike; Schneider, Dominik T.; Abele, Michael (European Journal of Pediatrics, 2022)
Very rare pediatric tumors (VRTs) pose a challenge for treating physicians as little is known about the best diagnostic assessment and therapeutic decision-making in these malignancies. A large proportion of these cancers occur in adolescence. Therefore, the established structures of pediatric oncology including cancer registration may partly be circumvented. This may lead to an underregistration in clinical cancer registries of yet unclear extent. The aim of this study is to increase the knowledge on the occurrence of VRTs in pediatric patients in Germany. Pseudonymized data of cases recorded in the Bavarian Cancer Registry (BCR) between 2002 and 2014 were retrieved. VRTs according to the definition of the European Cooperative Study Group for Pediatric Rare Tumors were identified using the ICD and ICD-O classification. The numbers of registered patients were compared to those reported to the German Childhood Cancer Registry (GCCR). 6.3% (n = 290) of all malignancies (n = 4615) in the age below 18 years were classified as VRTs. Median age at diagnosis was 15 years (range 0–17 years). The most common tumor types included malignant melanoma, skin carcinoma, and gonadal tumors. During the same period, 49 pediatric patients from Bavaria with matchable VRTs were reported to the GCCR, accounting for 17% of cases reported to the BCR. Conclusions: The frequency of VRTs in Germany is underestimated in the national GCCR. With this study, we present population-based data on the incidence of VRTs in Germany for the first time. In order to gain additional knowledge about these malignancies, registration of VRTs must be improved through enhanced data exchange between the GCCR, the public cancer registries, and the clinical Registry for Rare Pediatric Tumors (STEP).What is Known:• Rare pediatric tumors pose a challenge for treating physicians as limited knowledge is available on these malignancies for diagnostic and therapeutic decision-making.• Little is known about the frequency of these rare tumors in pediatric patients.What is New:• The frequency of rare pediatric tumors in Germany is distinctly underestimated in the German Childhood Cancer Registry.• We present population-based data on the incidence of these rare pediatric cancers for the first time.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Bavaria; Cancer registry; Germany; Incidence; Pediatric cancers; Rare tumors